Differentiating between Verbal and Spatial Encoding using Eye-Movement Recordings. Issue 9 (September 2013) - Lange, Elke B.; Engbert, Ralf
Visual information processing is guided by an active mechanism generating saccadic eye movements to salient stimuli. Here we investigate the specific contribution of saccades to memory encoding of verbal and spatial properties in a serial recall task. In the first experiment, participants moved their eyes freely without specific instruction. We demonstrate the existence of qualitative differences in eye-movement strategies during verbal and spatial memory encoding. While verbal memory encoding was characterized by shifting the gaze to the to-be-encoded stimuli, saccadic activity was suppressed during spatial encoding. In the second experiment, participants were required to suppress saccades by fixating centrally during encoding or to make precise saccades onto the memory items. Active suppression of saccades had no effect on memory performance, but tracking the upcoming stimuli decreased memory performance dramatically in both tasks, indicating a resource bottleneck between display-controlled saccadic control and memory encoding. We conclude that optimized encoding strategies for verbal and spatial features are underlying memory performance in serial recall, but such strategies work on an involuntary level only and do not support memory encoding when they are explicitly required by the task.